Inhibition of Collagen-Induced Platelet Aggregation by the Secobutanolide Secolincomolide A from Lindera obtusiloba Blume - Jung, Sang-Hyuk; Han, Joo-Hui; Park, Hyun-Soo; Lee, Jung-Jin; Yang, Seo Young; Kim, Young Ho; Heo, Kyung-Sun; Myung, Chang-Seon (Frontiers in Pharmacology, 2017)
Atherothrombosis is one of the main underlying cause of cardiovascular diseases. In addition to treating atherothrombosis with antithrombotic agents, there is growing interest in the role of natural food products and biologically active ingredients for the prevention and treatment of cardiovascular diseases. This study aimed to investigate the effect of secolincomolide A (3) isolated from Lindera obtusiloba Blume on platelet activity and identify possible signaling pathways. In our study, the antiplatelet activities of 3 were measured by collagen-induced platelet aggregation and serotonin secretion in freshly isolated rabbit platelets. Interestingly, 3 effectively inhibited the collagen-induced platelet aggregation and serotonin secretion via decreased production of diacylglycerol (DAG), arachidonic acid (AA), and cyclooxygenase (COX)-mediated metabolites such as thromboxane B2 (TXB2), and prostaglandin D2 (PGD2). In accordance with the antiplatelet activities, 3 prolonged bleeding time and attenuated FeCl3-induced thrombus formation in arterial thrombosis model. Notably, 3 abolished the phosphorylation of phospholipase Cγ2 (PLCγ2), spleen tyrosine kinase (Syk), p47, extracellular signal-regulated kinase 1/2 (ERK1/2), protein kinase B (Akt) by inhibiting the activation of the collagen receptor, glycoprotein VI (GPVI). Taken together, our results indicate the therapeutic potential of 3 in antiplatelet action through inhibition of the GPVI-mediated signaling pathway and the COX-1-mediated AA metabolic pathways.